The effect of concussion history on positional balance ability in rugby union athletes - Anyadike-Danes, K.; Brown, S. R. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Head traumas account for 29% of all injuries in professional rugby. Concussions are thought to have only a short-term effect on balance. The purpose of this study was to investigate whether concussion history affected a rugby team's ability to maintain balance and determine which sensory system was most affected. Thirty male academy rugby athletes separated into backs and forwards performed the m-CTSIB on the Biodex Balance SD system. The forwards, who had more rugby experience and concussions in comparison to the backs, produce substantially larger sway index scores (worse balance) in all four conditions. Useful future research could involve a longitudinal study which allowed baseline balance scores to be established and compared over time.